2017
DOI: 10.1002/chem.201605822
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Advanced Photosensitizers Based on Orthogonal BODIPY Dimers to Finely Modulate Singlet Oxygen Generation

Abstract: The synthesis, photophysical characterization, and modeling of a new library of halogen-free photosensitizers (PS) based on orthogonal boron dipyrromethene (BODIPY) dimers are reported. Herein we establish key structural factors in order to enhance singlet oxygen generation by judiciously choosing the substitution patterns according to key electronic effects and synthetic accessibility factors. The photosensitization mechanism of orthogonal BODIPY dimers is demonstrated to be strongly related to their intrinsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
107
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(120 citation statements)
references
References 31 publications
10
107
1
Order By: Relevance
“…Ortiz et al. confirmed that the intrinsic intramolecular CT character of the orthogonal BODIPY dimers was related to 1 O 2 generation . We considered that BODIPY‐MeAP in 1,4‐dioxane would follow a similar decay process to these BODIPY derivatives.…”
Section: Resultsmentioning
confidence: 91%
“…Ortiz et al. confirmed that the intrinsic intramolecular CT character of the orthogonal BODIPY dimers was related to 1 O 2 generation . We considered that BODIPY‐MeAP in 1,4‐dioxane would follow a similar decay process to these BODIPY derivatives.…”
Section: Resultsmentioning
confidence: 91%
“…For example, phenanthrene‐fused BODIPYs show red fluorescence ( λ FL =600–700 nm) and large ϵ values at the 0–0 transition ( ϵ 0–0 ≈60 000–140 000 m −1 cm −1 ) . Moreover, BODIPY derivatives with absorption and emission bands in the near‐infrared (NIR) region are also promising for photodynamic therapy (PDT) and two‐photon absorption (TPA) properties . However, little attention has been paid to a systematic discussion of structural and photophysical control, as well as large TPA properties, in the NIR region with regard to π‐extended BODIPY derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Unsubstituted BODIPY, for example, shows fluorescence efficiency near unity (0.97±0.03) and a long fluorescence lifetime of 6.89 ns in methanol, which leaves it little space to form the T 1 state. The heavy atom effect with iodine or bromine substitution and dimerization are often used to make BODIPY efficient in T 1 formation . By covalently linking an aryl as an electron‐donor unit (benzene, naphthalene, anthracene, or pyrene) onto the meso position of the BDP (Scheme ), we could make BODIPY compounds generate the T 1 state and hence singlet oxygen efficiently.…”
Section: Introductionmentioning
confidence: 99%